2023
DOI: 10.1186/s13023-023-02653-1
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian registry of patients with porphyria: REBRAPPO study

Abstract: Background Porphyrias are a rare group of disease due to inherited defects of heme synthesis with important systemic manifestations and great burden of disease for patients and families due to the exceptional course of disease with disabling chronic symptoms interposed by life-threatening acute attacks. Unfortunately, the porphyrias are usually underrecognized reflecting a lack of medical and disease awareness as well as few studies about natural history in large cohorts of patients. The main a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Acute attacks manifest as the classic triad of abdominal pain, neurological symptoms, and psychiatric abnormalities ( 5 ). An analysis of the REBRAPPO study, which examines Brazilian patients suffering from porphyria, reveals that among 148 individuals diagnosed with AHP, the most common initial clinical manifestations were abdominal pain in 77 patients (52.0%) and acute muscle weakness in 23 patients (15.5%) ( 7 ). Similarly, a prospective, multinational observational study of patients with recurrent AHP found that 92% of patients experienced abdominal pain, while 91% presented with a change in urine color.…”
Section: Discussionmentioning
confidence: 99%
“…Acute attacks manifest as the classic triad of abdominal pain, neurological symptoms, and psychiatric abnormalities ( 5 ). An analysis of the REBRAPPO study, which examines Brazilian patients suffering from porphyria, reveals that among 148 individuals diagnosed with AHP, the most common initial clinical manifestations were abdominal pain in 77 patients (52.0%) and acute muscle weakness in 23 patients (15.5%) ( 7 ). Similarly, a prospective, multinational observational study of patients with recurrent AHP found that 92% of patients experienced abdominal pain, while 91% presented with a change in urine color.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, a growing body of research has highlighted that individuals with AHPs experiencing sporadic attacks face substantial declines in their quality of life and exhibit a high frequency of chronic symptoms, resulting in a notable medical and economic burden (7,9,17,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of patients with AHPs, around 65-70% in large cohorts, experience chronic symptoms that markedly impair their quality of life, requiring extensive pharmacological treatment and clinical management, regardless of the number of attacks experienced throughout the course of the disease (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective, multinational, natural History study showed abdominal pain is the most common symptom during acute attacks (92%) ( Gouya et al, 2020 ), which is consistent with our results. However, the incidence of abdominal pain in the Chinese patients is significantly higher than that in Brazilian patients (77/172,52%) ( Souza et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%